2021
DOI: 10.3390/ma14112775
|View full text |Cite
|
Sign up to set email alerts
|

Green Approach to Develop Bee Pollen-Loaded Alginate Based Nanofibrous Mat

Abstract: Green electrospun materials are gaining popularity in the quest for a more sustainable environment for human life. Bee pollen (BP) is a valuable apitherapeutic product and has many beneficial features such as antioxidant and antibacterial properties. Alginate is a natural and low-cost polymer. Both natural materials show good compatibility with human tissues for biomedical applications and have no toxic effect on the environment. In this study, bee pollen-loaded sodium alginate and polyvinyl alcohol (SA/PVA) n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The peaks at 1731 cm −1 are typical of carboxylic acid dimers. The results are consistent with the literature [ 40 ].…”
Section: Resultssupporting
confidence: 93%
“…The peaks at 1731 cm −1 are typical of carboxylic acid dimers. The results are consistent with the literature [ 40 ].…”
Section: Resultssupporting
confidence: 93%
“…It comprises proteins, carbohydrates, lipids and amino acids under biologically acceptable conditions ( Anderson et al, 2014 ; Mohammad et al, 2021 ). There has not been any research on the development of bee pollen-loaded alginate-based nanomaterials or any type of polymeric nanofibers until Pakolpakçıl and Draczynski (in 2021) have hypothesised that combining bee pollen with alginate to create green nanofibrous materials might be a viable bioengineering option ( Pakolpakçıl and Draczynski, 2021 ). They used an electrospinning process to create Polish bee pollen-loaded alginate-based nanofibrous mats and studied their shape, chemical content and thermal characteristics.…”
Section: Alginate-based Nanomaterials For Biomedical and Pharmaceutic...mentioning
confidence: 99%
“…The authors indicated that the approach for producing bee pollen-loaded alginate-based nanofibrous material using green electrospinning of water-based systems might be an alternative. They showed how ecologically friendly nanofibrous materials might be created for a variety of uses, including biomedical applications, such as wound dressings and scaffoldings ( Pakolpakçıl and Draczynski, 2021 ).…”
Section: Alginate-based Nanomaterials For Biomedical and Pharmaceutic...mentioning
confidence: 99%
“…Natural bioactive agents have been used in biomedical due to their significant contribution since ancient times. Lately, the use of natural compounds such as plant extracts [21][22][23], bee products [24][25][26], and oils [27][28][29] for developing electrospun fibrous materials in biomedical applications has been studied extensively. Hypericum perforatum, a member of the Hypericaceae family, has long been regarded as a valuable herbal medicine.…”
Section: Introductionmentioning
confidence: 99%